Ultrasonic monitoring of zeolite A and Metal Organic Frameworks (MOFs) formations: A comparative study - Baser, Hasan-Hüseyin; Schwieger, Wilhelm (Studies in Surface Science and Catalysis, 2008)
We present in this work the use of ultrasonic attenuation (US-Attenuation) as a real-time, in-situ diagnostic tool for monitoring the crystallization of zeolites and MOFs. The results of this examination were analyzed with Avrami kinetic model. The reaction order (n) for the crystallization of CuBTC was found to be 0.91 while for that of zeolite A was 3.32.
Keywords: Zeolite Synthesis; MOF; Kinetic; Ultrasonic Attenuation